2021
DOI: 10.1186/s12877-021-02436-y
|View full text |Cite
|
Sign up to set email alerts
|

Digital personal assistants are smart ways for assistive technology to aid the health and wellbeing of patients and carers

Abstract: Background Digital health solutions such as assistive technologies create significant opportunities to optimise the effectiveness of both health and social care delivery. Assistive technologies include ‘low-tech’ items, such as memory aids and digital calendars or ‘high-tech’ items, like health tracking devices and wearables. Depending on the type of assistive devices, they can be used to improve quality of life, effect lifestyle improvements and increase levels of independence. Acceptance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 29 publications
(27 reference statements)
1
47
0
1
Order By: Relevance
“…One study ( 30 ) has suggested that online psychoeducational support and specific guidelines for care can meet caregivers' needs and contribute to their well-being. The use of technology by people with dementia and their caregivers depends on expectations, perceived skills, and expertise in using the devices ( 34 ). Some studies ( 12 , 15 ) reported that many people with dementia were less likely to be digitally literate, making equal access to the services difficult.…”
Section: Discussionmentioning
confidence: 99%
“…One study ( 30 ) has suggested that online psychoeducational support and specific guidelines for care can meet caregivers' needs and contribute to their well-being. The use of technology by people with dementia and their caregivers depends on expectations, perceived skills, and expertise in using the devices ( 34 ). Some studies ( 12 , 15 ) reported that many people with dementia were less likely to be digitally literate, making equal access to the services difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, emerging evidence has demonstrated that voice-activated smart speakers have potential benefits in assisting older adults with activities and providing companionship. 25 , 26 Altogether, these findings suggest that adopting socially assistive technologies, including care robots may be beneficial for promoting the well-being of older adults, especially those living alone and those with dementia. However, concerns relating to the use of care robots, initial anxiety or fear, 27 or privacy issues, exist.…”
Section: Discussionmentioning
confidence: 89%
“…The goal of this project is to produce engineers from technical colleges across the country who can realize "the creation of a symbiotic society by using eAT even for people with disabilities" [13]. These pilot initiatives that incorporate new technologies to extend healthy life expectancy and improve wellbeing are at the beginning stages of consideration as a challenge not only for Japan but also for the world [14,15].…”
Section: Gear 50 Project and Eat(extended Assistive Technology)mentioning
confidence: 99%